Atopic Diseases and Subsequent Ischemic Stroke Among Patients With Schizophrenia: A Nationwide Longitudinal Study. Issue 9 (November 2015) - Chen, Mu-Hong; Li, Cheng-Ta; Hsu, Ju-Wei; Huang, Kai-Lin; Lin, Wei-Chen; Chang, Wen-Han; Chen, Tzeng-Ji; Pan, Tai-Long; Su, Tung-Ping; Bai, Ya-Mei
ABSTRACT: Background: Chronic inflammation plays an important role in schizophrenia and atopic diseases, and studies have suggested that chronic inflammation is associated with an increased risk of stroke. The role of atopic diseases in the development of stroke among patients with schizophrenia is still unknown. Methods: A total of 63, 913 patients with schizophrenia without a stroke history between 2002 and 2008 and 63, 913 age- and sex-matched controls were included and followed up to the end of 2011. Patients with schizophrenia and the reference group were divided into subgroups based on the presence or absence of atopic diseases. Individuals who developed stroke during follow-up were identified. Results: Patients with schizophrenia had an increased risk of developing ischemic stroke (no atopic disease: hazard ratio [HR] = 2.18, 95% confidence interval [CI] = 1.88–2.53; with atopic disease: HR = 3.11, 95% CI = 2.63–3.69) compared with the reference group without atopic diseases. Among patients with schizophrenia, the presence of atopic diseases increased the risk of developing ischemic stroke (HR = 1.44, 95% CI = 1.24–1.66), with a cumulative relationship between greater numbers of atopic comorbidities and a greater risk of ischemic stroke (one atopic disease: HR = 1.39, 95% CI = 1.19–1.63; two atopic comorbidities: HR = 1.48, 95% CI = 1.10–2.00; at least 3 atopic comorbidities: HR = 2.81, 95% CI = 1.55–5.12). Conclusions: The combined presence of schizophrenia and atopic diseases is associated with an increased risk of ischemic stroke in later life compared with individuals without these conditions. Abstract : Supplemental digital content is available in the text.